Agroforestry systems: helping smallholders adapt to climate risks while mitigating climate change. (28th August 2014) - Lasco, Rodel D.; Delfino, Rafaela Jane P.; Espaldon, Marya Laya O.
<x xml:space="preserve">Abstract</x> There is increasing interest to combine adaptation and mitigation measures that provide win–win solutions to climate change. Agroforestry systems offer compelling synergies between adaptation and mitigation. This article reviews the empirical evidence from various studies on how trees and agroforestry systems enhance smallholders' capacity to adapt to climate risks. Agroforestry systems improve resilience of smallholder farmers through more efficient water utilization, improved microclimate, enhanced soil productivity and nutrient cycling, control of pests and diseases, improved farm productivity, and diversified and increased farm income while at the same time sequestering carbon. Although these seems very promising, tradeoffs may arise both at the farm and landscape scales. WIREs Clim Change 2014, 5:825–833. doi: 10.1002/wcc.301 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.